Escherichia coli Bacteria Test on Polluted Meatballs With Several Variations of Positive Control Concentration: Escherichia coli Bacteria Test on Polluted Meatballs With Several Variations of Positive Control Concentration - Alfi sophian (BiosciED: Journal of Biological Science and Education, 2022)
Escherichia coli bacteria test on contaminated meat processed food products with several variations of positive control concentrations was carried out to provide additional information about determining the LOD value in the test method for the detection of Escherichia coli pathogenic bacteria. The purpose of this study was to detect and identify bacterial contamination of Escherichia coli ATCC 25922 in contaminated meat processed food products with variations in the concentration of positive control. The method used to identify is the enrichment method, using enrichment media to grow the suspected target bacterium Escherichia coli ATCC 25922 spiked in meat-processed food products, followed by isolation using selective media and ending with confirmation and affirmation tests. The samples used were 10 packages of processed meat food products. The samples were then spiked using various concentrations of positive control Escherichia coli 5, 10, 50, and 100 colonies/gr. The data from the research showed that all samples from the treatment of variations in the concentration of spike positive controls were detected and identified the presence of Escherichia coli ATCC 25922. Based on the results of this study, it can be concluded that all samples spiked with various variations in the concentration of positive control were detected and identified Escherichia coli ATCC 25922.